EFFECT OF TIMINOR AND RATES OF POTASSIUM ON BREAD WHEAT QUALITY AND SOME OTHER CHARACTERES - & et al, Zeboon (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field experiment was conducted at the experimental farm, Dept. of Field Crop, Coll. of Agriculture, Univ. of Baghdad ,during 2011-2012, to study the effect of potassium fertilizer levels and appilication stage on bread wheat grains quality Triticum asetivum L.(Var- Abu-Ghraib-3) and some other characteres . Factorial experiment was conducted in RCBD design with three replication involved two levels of potassium 120,180 kg.ha-1 and control treatment the second factor was three stage of application  (tillering ,Booting , flowering). The results shows non significant differ between potassium leveles for all studied traits, except havest index.The potassium level 180 kg.ha-1 produced plants with highest harvest index (38.17%), in comparison to the level 120 kg.ha-1, (36.82%).The application stage at flowering time produced grains with higher protein (12.18%), when compard to the tillering and booting stages (11.32% and 12.17%) respectively. The potassium application stage at tillering was superior in protein yield and harvest index 0.935 mg.ha-1 and 40.37%, respectively. It can be conclude that potassium addition stage was more important than, it,s dosages.